Downregulation of the ACE2/Ang-(1–7)/Mas axis in transgenic mice overexpressing GH - Muñoz, Marina Cecilia (2014)
The renin–angiotensin system (RAS) plays a crucial role in the regulation of physiological homeostasis and diseases such as hypertension, coronary artery disease, and chronic renal failure. In this cascade, the angiotensin-converting enzyme (ACE)/angiotensin II (Ang II)/AT1 receptor axis induces pathological effects, such as vasoconstriction, cell proliferation, and fibrosis, while the ACE2/Ang-(1–7)/Mas receptor axis is protective for end-organ damage. The altered function of the RAS could be a contributing factor to the cardiac and renal alterations induced by GH excess. To further explore this issue, we evaluated the consequences of chronic GH exposure on the in vivo levels of Ang II, Ang-(1–7), ACE, ACE2, and Mas receptor in the heart and the kidney of GH-transgenic mice (bovine GH (bGH) mice). At the age of 7–8 months, female bGH mice displayed increased systolic blood pressure (SBP), a high degree of both cardiac and renal fibrosis, as well as increased levels of markers of tubular and glomerular damage. Angiotensinogen abundance was increased in the liver and the heart of bGH mice, along with a concomitant increase in cardiac Ang II levels. Importantly, the levels of ACE2, Ang-(1–7), and Mas receptor were markedly decreased in both tissues. In addition, Ang-(1–7) administration reduced SBP to control values in GH-transgenic mice, indicating that the ACE2/Ang-(1–7)/Mas axis is involved in GH-mediated hypertension. The data indicate that the altered expression profile of the ACE2/Ang-(1–7)/Mas axis in the heart and the kidney of bGH mice could contribute to the increased incidence of hypertension, cardiovascular, and renal alterations observed in these animals.